2024
DOI: 10.1093/gigascience/giad103
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary genomics of three agricultural pest moths reveals rapid evolution of host adaptation and immune-related genes

Yi-Ming Weng,
Pathour R Shashank,
R Keating Godfrey
et al.

Abstract: Background Understanding the genotype of pest species provides an important baseline for designing integrated pest management (IPM) strategies. Recently developed long-read sequence technologies make it possible to compare genomic features of nonmodel pest species to disclose the evolutionary path underlying the pest species profiles. Here we sequenced and assembled genomes for 3 agricultural pest gelechiid moths: Phthorimaea absoluta (tomato leafminer), Keiferia lycopersicella (tomato pinwor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 99 publications
0
1
0
Order By: Relevance
“…The use of genomic data has revolutionized our understanding of the natural world. In particular, understanding genomic phenomena such as the expansion and contraction of gene families, which comprise a set of genes that tend to exhibit functional similarity [ 25 , 26 ], can provide relevant insights into functional aspects of organisms [ 27 , 28 ]. For example, it has been demonstrated that the genomes of the German cockroach and house fly, among all sequenced insects, have the largest repertoires of sensory receptors within the insect pickpocket gene family, which are responsible for detecting certain environmental stimuli such as water and salt [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of genomic data has revolutionized our understanding of the natural world. In particular, understanding genomic phenomena such as the expansion and contraction of gene families, which comprise a set of genes that tend to exhibit functional similarity [ 25 , 26 ], can provide relevant insights into functional aspects of organisms [ 27 , 28 ]. For example, it has been demonstrated that the genomes of the German cockroach and house fly, among all sequenced insects, have the largest repertoires of sensory receptors within the insect pickpocket gene family, which are responsible for detecting certain environmental stimuli such as water and salt [ 29 ].…”
Section: Introductionmentioning
confidence: 99%